Evaluación de ensilajes de maíz con diferentes niveles de alfalfa en la alimentación de ovinos de la Quinta Experimental Punzara de la Universidad Nacional de Loja - Cevallos Cevallos, Jhandry Israel (2015)
This work was carried out in the “Punzara” Experimental Farm of the National University of Loja, with the aim of evaluating the effect of using corn silage and alfalfa in the diet of sheep. Three percentages of alfalfa (10%, 20% and 30%) in the corn silage were studied; the test was conducted over a 90 day period with 16 mixed race sheep (Corriedale x Pool Dorset) distributed over four experimental groups using a randomized block design with four animals respectively, each animal being an experimental unit. The silage was stored in 40 kg plastic bags and fermentation time lasted 30 days. The nutritional value was assessed using a chemical composition analysis; and after an adjustment period of 7 days, the animals were provided the dry feed, an amount equivalent to 30% of their daily intake according to established treatments; as follows: T1 (10%), T2 (20%), T3 (30%) and T4 (Control). The variables evaluated were: feed intake, weight gain, feed conversion, yield, nutritional value and palatability of the silage. The results demonstrated that treatment two recorded higher consumption of dry feed silage with 34.47 kg on average per animal. The biggest daily gain weight daily was attained using the same treatment with 79.44 g / day; whilst the third treatment resulted in the best feed conversion to 6.86. The percentage of palatability was superior with treatment one with a percentage of 79.39%. We concluded that the silage made up from the corn shaft with the different percentages of alfalfa possessed good palatability and acceptable nutritional value, which was reflected in the level of consumption and productive performance; and so was considered an alternative food supplement for grazing sheep. Keywords: silage, corn, alfalfa, fermentation, nutritional supplement, sheep.